Drugs repurposed: An advanced step towards the treatment of breast cancer and associated challenges - Malik, Jonaid Ahmad; Ahmed, Sakeel; Jan, Bisma; Bender, Onur; Al Hagbani, Turki; Alqarni, Aali; Anwar, Sirajudheen (Biomedicine & pharmacotherapy, 2022)
Breast cancer (BC) is mostly observed in women and is responsible for huge mortality in women subjects globally. Due to the continued development of drug resistance and other contributing factors, the scientific community needs to look for new alternatives, and drug repurposing is one of the best opportunities. Here we light upon the drug repurposing with a major focus on breast cancer. BC is a division of cancer known as the leading cause of death of 2.3 million women globally, with 685,000 fatalities. This number is steadily rising, necessitating the development of a treatment that can extend survival time. All available treatments for BC are very costly as well as show side effects. This unfulfilled requirement of the anti-cancer drugs ignited an enthusiasm for drug repositioning, which means finding out the anti-cancer use of already marketed drugs for other complications. With the advancement in proteomics, genomics, and computational approaches, the drug repurposing process hastens. So many drugs are repurposed for the BC, including alkylating agents, antimetabolite, anthracyclines, an aromatase inhibitor, mTOR, and many more. The drug resistance in breast cancer is rising, so reviewing how the challenges in breast cancer can be combated with drug repurposing. This paper provides the updated information on all the repurposed drugs candidates for breast cancer with the molecular mechanism responsible for their anti-tumor activity. Additionally, all the challenges that occur during the repurposing of the drugs are discussed. [Display omitted] •BC is a division of cancer known as the leading cause of death in women globally, and second, in the US, roughly 50% of the women without known risk factors suffered from BCs.•The primary cause of death due to BC is the resistance to conventional chemotherapeutic agents responsible for recurrence and relapse of cancer, despite various advancements in breast cancer therapy.•The drug purposing against BC explores the therapeutic use of existing clinically approved, off-patent drugs with known targets for another indication to minimize the cost of therapy, time, and risk.•Drug repurposed against BC with existing knowledge of molecular targets can be an excellent approach towards treatment.